2010
DOI: 10.1186/bcr2499
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 is a transcriptional target of ERα and has a critical role in breast cancer endocrine sensitivity and resistance

Abstract: not available at time of publication. Abstract not available at time of publication. Retrospective studies on male breast cancer (MBC) have suff ered from small numbers of cases available from any one centre; thus a signifi cant problem in eff ectively studying this disease is accruing suffi ciently large numbers to allow comparative analysis of biomarkers associated with response. Using a coordinated multicentre approach, we present the fi rst large-scale study to address the relevance of the expression of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…FOXM1 emerges as a potent oncogenic transcription factor closely involved in resistance to agents used in chemotherapeutic protocols in breast cancer (Carr et al, 2010;Kwok et al, 2010;Millour et al, 2010;Park et al, 2012;Khongkow et al, 2014). Although FOXM1 activates genes crucial for metastasis, angiogenesis, invasion and DNA repair , its role in the regulation of genes involved in survival and inhibition of apoptosis has not been explored.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…FOXM1 emerges as a potent oncogenic transcription factor closely involved in resistance to agents used in chemotherapeutic protocols in breast cancer (Carr et al, 2010;Kwok et al, 2010;Millour et al, 2010;Park et al, 2012;Khongkow et al, 2014). Although FOXM1 activates genes crucial for metastasis, angiogenesis, invasion and DNA repair , its role in the regulation of genes involved in survival and inhibition of apoptosis has not been explored.…”
Section: Discussionmentioning
confidence: 98%
“…FOXM1 overexpression is a common feature of most tumours , and often correlates with drug resistance (Carr et al, 2010;Kwok et al, 2010;Millour et al, 2010;Park et al, 2012;Khongkow et al, 2014) and poor outcome in breast cancer patients' samples (Martin et al, 2008;Yau et al, 2011). Apart from cell cycle genes, FOXM1 can transcriptionally activate genes involved in many other processes like angiogenesis (Ahmad et al, 2010;Karadedou et al, 2012), invasion (Ahmad et al, 2010), metastasis (Raychaudhuri and Park, 2011) and DNA damage repair Zona et al, 2014).…”
mentioning
confidence: 98%
“…It was first identified as a proliferation-specific transcription factor, which is expressed in various tumor cell lines and embryonic tissues [41,42]. Previous work has linked FoxM1 upregulation to a variety of cancers, including cancers of the liver, gastric, prostate, brain, breast, lung, esophagus, colon, pancreas and nervous system, marking it as a proto-oncogene [13,[18][19][20][21][22][23][24][25][26][27]43]. Genome-wide gene expression profiling of cancers has independently and consistently identified FoxM1 as one of the most commonly upregulated genes in human solid tumor [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to play important roles in regulating the expression of genes involved in cell proliferation, differentiation, and transformation [17]. Increased expression of FoxM1 has been found in several human tumors suggesting a role in human carcinogenesis [13,[18][19][20][21][22][23][24][25][26][27]. Moreover, it has been shown that higher expression of FoxM1 was associated with poor prognosis of cancer patients and could serve as an independent predictor of poor survival in cancer [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…FoxM1 levels were dramatically decreased in adult tissues, but FoxM1 expression was reactivated by oncogenic signaling pathways and reactive oxygen species, resulting in the malignant progression of numerous cancers [10,11]. We had previously reported that hypoxia induced FoxM1 expression and FoxM1 overexpression accelerated the growth and survival of cancer cells under hypoxic stress [12].…”
Section: Introductionmentioning
confidence: 97%